Education and Social Exclusion of Children With Chronic Diseases: The Case of Schooling Within Greek Hospitals - Kontogianni, Vassiliki; Tourtouras, Christos; Kyridis, Argyris; Pehlivanou, Eleni (International Research in Education, 2021)
This research attempts to identify effective teaching strategies, as well as any barriers encountered in the education of children with chronic diseases. In addition, it attempts to probe the conditions under which the children are being taught after hospitalization. The research data was collected after a series of interviews with parents whose children had been hospitalized for a long time with a serious illness and teachers who had worked in hospital schools or had received a child after hospitalization. The findings of the study show that hospital education has gaps in curriculum content and that significant government attention is needed on program and material infrastructure issues. It also emphasizes the inadequate training of teachers about chronic diseases as well as the approach of children who are reintegrated into school life after a long absence.